Mapping energy use portfolios and household welfare in India: Insights from farm and household surveys in Bihar and Jharkhand - Sufian, Farha; Alvi, Muzna; Beniwal, Ezaboo (International Food Policy Research Institute, 2024)
Energy use in India plays a critical role in shaping the country’s sustainable development trajectory, particularly in the context of the water-energy-food-environment nexus. As the world’s most populous nation with a rapidly growing economy, India faces significant challenges and opportunities in transitioning to cleaner and more efficient energy systems. The country’s energy access and use portfolio is closely linked to agricultural productivity, household well-being, and environmental sustainability, making it a key area for policy interventions. Access to clean and reliable energy is essential for improving food security, enhancing economic opportunities, and empowering marginalized communities, particularly women. However, India’s energy landscape is diverse, with rural areas heavily reliant on traditional energy sources like firewood and kerosene, while urban regions increasingly adopt modern energy technologies.